The body within the school: necessary mappings - Farah, Marisa Helena Silva (Paidéia (Ribeirão Preto), 2010)
This paper proposes to map students' bodies in schools in the attempt to enable beginner educators to build a view of students with their bodies, and also to encourage educators to find their place in this context with their own bodies. The analysis of two interdependent axes: (1) concept of body-subject, and (2) space and time of the body in school, is expected to contribute to the educational discussion, by demonstrating how the curriculum, didactics, and evaluation, among other elements can signal considerations assigned to the body. The study concludes revealing the paradox represented by these same elements when defined by power relations.